Evaluation Study of Patients Infected with Chronic Hepatitis C in Iraq - Muhsun, Laith H.; Al-Akayshi, ., Ragad J.; Mhawes, Ali A. (AL-Kindy College Medical Journal, 2015)
Background: ;Hepatitis C virus (HCV) is a major cause of chronic liver disease. Approximately 85% of patients acutely infected with HCV progress to chronic liver disease with persistence of HCV-RNA for more than 6 months Among patients with chronic HCV infection , 15-20% progress to end-stage liver disease main transmission methods of the virus is by : blood and blood products ; sharing needles and acupuncture .Objective: To evaluate Iraqi patients infected with chronic HCV, including their treatment, and factors that affect their response to treatment .Methods :This study was performed at Gastroenterology and Hepatology hospital in Baghdad from January 2011 to March 2012.The study enrolled 90 patients with HCV Antibody positive (Ab +ve) , every patient subjected to thorough history taking and clinical examination, and complete investigations , some of the patients subjected to liver biopsy which is analyzed by Ishak classification , the data analyzed by chi square and P value